2015
DOI: 10.1038/onc.2015.310
|View full text |Cite
|
Sign up to set email alerts
|

The TWEAK receptor Fn14 is a potential cell surface portal for targeted delivery of glioblastoma therapeutics

Abstract: Fibroblast growth factor-inducible 14 (Fn14; TNFRSF12A) is the cell surface receptor for the tumor necrosis factor (TNF) family member TNF-like weak inducer of apoptosis (TWEAK). The Fn14 gene is normally expressed at low levels in healthy tissues but expression is significantly increased after tissue injury and in many solid tumor types, including glioblastoma (GB; formerly referred to as ‘glioblastoma multiforme’ or GBM). GB is the most common and aggressive primary malignant brain tumor, and the current sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 182 publications
(273 reference statements)
5
77
0
Order By: Relevance
“…We recently reported that the highest level of Fn14 mRNA expression occurred in mesenchymal subtype tumors [4]. However, this prior analysis utilized a relatively small GBM subtype sample size and did not distinguish between IDH1 WT and R132H mutant tumors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently reported that the highest level of Fn14 mRNA expression occurred in mesenchymal subtype tumors [4]. However, this prior analysis utilized a relatively small GBM subtype sample size and did not distinguish between IDH1 WT and R132H mutant tumors.…”
Section: Resultsmentioning
confidence: 99%
“…In the setting of glioblastoma (GBM), the most prevalent and lethal form of adult brain cancer [6, 7], elevated Fn14 expression is associated with poor patient survival [8]. Four major transcriptional subtypes of GBM— classical, mesenchymal, neural and proneural—have been identified [911] and we reported previously that Fn14 mRNA was expressed at the highest levels in the more invasive and aggressive mesenchymal subtype tumors [4]. Glioma cell invasion into normal brain parenchyma is a hallmark of GBM pathophysiology and generally leads to tumor recurrence [6, 7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…NPs targeted to Fn14-positive GBM cells using a monoclonal antibody improved NP tumor localization and internalization. 48,68 Thus, a similar targeting strategy may enhance the delivery of platinum compounds specifically to GBM cells, improving efficacy and minimizing toxicity.…”
Section: Reduced Side-effects Through Enhanced Site-specific Deliverymentioning
confidence: 99%